Investigation and performance analysis of solar still with energy storage materials: An energy- exergy efficiency analysis. (January 2022) - Mevada, Dinesh; Panchal, Hitesh; Ahmadein, M.; Zayed, Mohamed E.; Alsaleh, Naser A.; Djuansjah, Joy; Moustafa, Essam B.; Elsheikh, Ammar H.; Sadasivuni, Kishor Kumar
Abstract: Researchers have attempted different Energy storage materials (ESM) in solar stills (SS) to improve distillate yield. In this experimental work, an attempt was made to increase the distillate yield & efficiency of SS, using good absorbing and heat transfer capacity of ESM. A comparison was made between a conventional solar still (CSS) and a solar still with energy storage materials (SSWESM) in this experiment. Different energy storage materials like black color glass ball (BCGB), black granite (BG) and white marble stone (WMS) were used in equal quantity during experimental work. CSS and SSWESM had daily distillate yield of 1.4 kg/m2 and 2.5 kg/m2, respectively. The ESM boosts water evaporation during the day and releases heat at night, resulting in a higher distillate yield than CSS. Meanwhile, the exergy efficiency (ƞ exe ) of CSS and SSWESM were 4.99% and 12.55% respectively. Also the SSWESM gives 72.6% more daily efficiency (ƞ) than CSS.